PENGEMBANGAN E-MODUL BERBASIS BOOK CREATOR BERDASARKAN GAYA BELAJAR PADA MATERI KESEBANGUNAN - Liyati, Nuril; Ilmi, Noraniza Bahratul (Universitas Batanghari Jambi, 2025)
This research aims to produce valid and practical e-modules based on learning styles that can help educators and learners in implementing math learning. Educators and students in carrying out mathematics learning. The development of this e-module is included in the Research and Development (R&D) research that refers to the ADDIE model consisting of and Development (R&D) development research that refers to the ADDIE model which consists of five phases, namely: analysis, design, development, implementation, and evaluation. The instruments used are material expert validation sheets and media expert validation sheets. media experts and student response questionnaires. The analysis technique used analysis is the validity analysis and practicality analysis of e-modules. E-module has been designed and developed based on the analysis process. Trial test readability and implementation of e-modules have been carried out. The results of this research are the e-modules that have been developed are generally feasible to use. To be used. This is indicated by the average results of the assessment of material and media experts' assessment of the e-modules reached 86.5% with the criteria of “very valid, as well as the results of the student response questionnaire which obtained a score of 88.125% with the criteria “very practical”. These results indicate that the e-module e-module that has been developed can be used as an alternative teaching material that is adapted to the learning style of students. teaching materials that are tailored to the learning style of students.